Improving School-Age Children's Knowledge on Coughing and Sneezing Ethics through Linear Multimedia - Feny Dwi Aprilia; Taufan Arif; Nurul Hidayah; Tri Nataliswati (STIKes Patria Husada Blitar, 2023)
School-age children's knowledge of cough and sneeze etiquette is mostly in the low category. Cough and sneeze etiquette looks very simple, but most children admitted that they do not know and understand how to apply proper cough and sneeze etiquette. One of the recommended ways to prevent the spread of infection is to cover the mouth and nose when coughing and sneezing or often referred to as cough and sneeze etiquette. This study aimed to determine the effect of linear multimedia on students' knowledge about cough and sneeze ethics at SDN IV Tapan Tulungagung Regency. The design of the study used Quasy Experiment (pseudo experiment). The sampling technique used non-probability sampling; purposive sampling technique. Comparison of knowledge values between the pre-test and post-test indicated that there was a significant difference between the level of knowledge before and after being given education on cough and sneeze ethics through linear multimedia. Through those results, it can be concluded that there is an effect of linear multimedia on students' knowledge and attitudes about cough and sneeze ethics at SDN IV Tapan Tulungagung Regency. Therefore, linear multimedia can be used as a suitable educational media for school-age children